Undiagnosed liver diseases - Gao, Emily (Transl Gastroenterol Hepatol, 2021)
The landscape of chronic liver disease has drastically changed over the past 20 years, largely due to advances in antiviral therapy and the rise of metabolic syndrome and associated non-alcoholic fatty liver disease (NAFLD). Despite advances in the diagnosis and treatment of a variety of liver diseases, the burden of chronic liver disease is increasing worldwide. The first step to addressing any disease is accurate diagnosis. Here, we discuss liver diseases that remain undiagnosed, either because they are difficult to diagnose or due to hepatic manifestations of an unrecognized systemic disease. Additionally, their underlying etiology may remain unknown or they represent previously uncharacterized and therefore novel liver diseases. Our goal is to provide a framework for approaching undiagnosed liver diseases which elude standard hepatic diagnostic work-up and whose patterns of disease are often overlooked.